Japan cranks up download speeds [DSL technology]. - Boyd, J. (IEEE spectrum)
Japan has caught up in the competitive high-speed Internet technologies thanks to the efforts of billionaire entrepreneur Masayoshi Son and his Softbank Corp, by deploying ADSL (asymmetric digital subscriber line) technology in its fixed-line telephone networks. Though Japan still lags far behind some other countries in broadband penetration, it now tops the world in providing the cheapest DSL services. Through the years, Son has made advancement in the technology introducing Internet protocol-based telephone service (IP phone), fixed-line services, broadband and mobile services, but because of competition in the technology market his telecom strategy is still to be erect, at a maximum speed to a little lower price compared to the competition.